Importancia del reconocimiento de los activos biológicos en los estados financieros (2023)
The purpose of this article is to explain the importance of recognizing biological assets in financial statements. Biological assets play a significant role in the Colombian economy and in the financial sphere of companies operating in the country. These assets, which include plantations, livestock, crops, and renewable natural resources, are of strategic importance to various sectors, including agriculture, livestock, and the forestry industry. In order to guarantee the transparency and comparability of the financial statements of Colombian companies with international standards, the International Financial Reporting Standards (IFRS) are applied, adopted by Colombia through Decree 2784 of 2012. These standards provide specific guidelines for the recognition, measurement, presentation, and disclosure of biological assets.